Pengembangan Sumber Daya Manusia (Sdm) Melalui Kemampuan Berbahasa Inggris Di Panti Asuhan At-Thoibah Aisyiyah Kelurahan Pane Kecamatan Rasa Na’e Barat Kota Bima - Hermanto, Lubis; Rosadi, Ariani; Putri, Nunung; Adiningsih, Jumiati (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
The desire to increase the effectiveness of the success of non-formal education has carried out various evaluations of the progress of non-formal education so far. Countries that are members of UNESCO have concluded that the development of non-formal education must be participatory as much as possible, implemented by the community itself and the government's role should be positioned more as a facilitator.Formal education and the school system are apparently not enough to answer the various problems faced by society. This can be seen from the low level of public education, the high level of illiteracy for adults, the high level of unemployment, the high level of poverty and so on. Meanwhile, government policy in educational development places great emphasis on formal education and the school system. The attention to non-formal education is still very limited. This can be seen from the allocation of budgets and facilities as well as various other resources which are much greater devoted to formal education and the school system.In terms of the human achievement index (HDI), Bima City, even though it is ranked 2nd (second) contributor to the smallest poverty rate after Mataram City, still has quite big problems, based on data from the Bima City Education and Youth Service in 2015, in Bima City there are still 48% of people of productive age. age range 16-23 years who have not received education from various levels of education. Of course this is a serious problem.Bima City, as an autonomous region in its development, has begun to establish a non-formal education center in Bima City. The scope and variety of forms of activities currently not only take the form of the activities described above, but also organize various formal out-of-school educational activities that are oriented towards the abilities of students who have skills, these various activities start from Life Skills (Education). Life Skills) and courses, so today's educational activities cannot be underestimated, which for some people is considered only oriented towards providing equivalent diplomas to people who do not have the opportunity or are forced to leave their formal education.Efforts that are being promoted by the central government, including the Bima City government, through leading sectors that deal with these problems continue to try to promote programs that are felt to be able to unravel the common thread of poverty and educational backwardness, however there is an interrelated correlation between Educational progress is seen from the level of educational participation and poverty. One of these efforts is of course by raising public awareness to receive education, even though not through formal channels (school).